Distributed Systems Meet Economics: Pricing in the Cloud - Wang, Hongyi; Jing, Qingfeng; He, Bingsheng; Qian, Zhengping; Zhou, Lidong (HotCloud '10, 2010)
Cloud computing allows users to perform computation in a public cloud with a pricing scheme typically based on incurred resource consumption. While cloud computing is often considered as merely a new application for classic distributed systems, we argue that, by decoupling users from cloud providers with a pricing scheme as the bridge, cloud computing has fundamentally changed the landscape of system design and optimization. Our preliminary studies on Amazon EC2 cloud service and on a local cloud computing testbed, have revealed an interesting interplay between distributed systems and economics related to pricing. We believe that this new angle of looking at distributed systems potentially fosters new insights into cloud computing.